2017
DOI: 10.1093/ntr/ntw396
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pack warning labels on quitting and related thoughts and behaviours in a national cohort of Aboriginal and Torres Strait Islander smokers

Abstract: Graphic warning labels are likely to be effective for Aboriginal and Torres Strait Islander smokers as they are for the broader Australian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Nationwide programmes that are aimed at preventing tobacco use by means of taxation, introduction of smoke free workplaces, and prohibition of tobacco advertising were also found to be effective in Indigenous populations in the USA, Australia, and New Zealand, and were generally well accepted by the communities involved (appendix). [162][163][164][165][166][167]…”
Section: Western Pacificmentioning
confidence: 99%
“…Nationwide programmes that are aimed at preventing tobacco use by means of taxation, introduction of smoke free workplaces, and prohibition of tobacco advertising were also found to be effective in Indigenous populations in the USA, Australia, and New Zealand, and were generally well accepted by the communities involved (appendix). [162][163][164][165][166][167]…”
Section: Western Pacificmentioning
confidence: 99%
“…Confounding was predominately due to introduction of enhanced pictorial health warnings [ 3 , 35 ], other marketing campaigns and smoking policies (e.g. price increases) during the course of the longitudinal study [ 34 , 48 ], or due to variance in smoking quantity amongst participants [ 32 , 38 , 51 ]. One study was found to be serious in at least one domain [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some key examples are initiatives that address tobacco use, heavy drinking and diabetes in Aboriginal peoples and Torres Strait Islanders in Australia [80][81][82][83].…”
Section: Discussionmentioning
confidence: 99%